Reduction of Black Carbon Emissions from Residential Wood Combustion in the Arctic. Black Carbon Inventory, Abatement Instruments and Measures. (DRAFT) - Arctic Contaminants Action Program (ACAP) (Arctic Contaminants Action Program (ACAP), 2014)
Black carbon and other short-lived climate forcers is a topic of great interest to the Arctic Council. In addition to establishing specific Task Forces to develop policy recommendations for subsequent ministerial meetings, the Ministerial Meetings in 2009 and 2011 decided to: “Urge implementation of early actions where possible on methane and other short-lived climate forcers” (Tromsø, Norway 2009) And “Encourage Arctic states to implement, as appropriate in their national circumstances, relevant recommendations for reducing emissions of black carbon” (Nuuk, Greenland 2011). The Arctic Contaminants Action Program (ACAP) Working Group under the Arctic Council followed suit by establishing a Project Steering Group on black carbon and other short-lived climate forcers and contaminants (SLCFs) in 2010. The steering group was mandated to facilitate projects on activities that reduce emissions of black carbon which are transported to and deposited in the Arctic. The work on SLCFs was continued and strengthened at the 2013 Arctic Council Ministerial Meeting in Kiruna, where the Ministers recognized that: “reduction of short-lived climate forcers could slow Arctic and global climate change and have positive effects on health, and welcome the report on short- lived climate forcers, and support its recommendations including that national black carbon emission inventories for the Arctic should continue to be developed and reported as a matter of priority”, and decided to “establish a Task Force to develop arrangements on actions to achieve enhanced black carbon and methane emission reductions in the Arctic, and report at the next Ministerial meeting in 2015”. This project on Black Carbon Emission Reductions from Residential Wood Combustion was brought forward on the basis of the Ministerial Declarations in 2009 and 2011 and is part of the project portfolio under ACAP WG and the SLCFC PSG. The project has been co-financed by the Norwegian Ministry of Foreign Affairs and the Finnish Ministry of the Environment, and is ...